The effectiveness of using SMS instalment alert platform on customer satisfaction in the retail clothing stores in Zimbabwe - Douglas Chiguvi; Collen Mahambo; Keofe Tender Kgetho (Dutch Journal of Finance and Management, 2020)
The study was focusing on the effectiveness of using (SMS) instalment platform as a way of meeting customer satisfaction at Edgars stores Ltd in Zimbabwe. The main objective of the research was to measure the effectiveness of SMS installment platform on customer satisfaction. Causal research design was employed and a simple random sampling technique was used in selecting the respondents. Questionnaires were used to gather data from a sample size of 357 consisting of 342 customers and 15 staff members of Edgars' stores Ltd. The data collected was analyzed through the use of SPSS version 20 in order to determine the strength of the relationship and the moderating effect. The data findings were presented in form of tables. The research findings from the hypothesis tests explored that there is a strong significant and positive relationship between SMS installment platform service and customer satisfaction. The study recommended the company to use SMS platform for other promotion activities like sending bonus vouchers, news release and advertisements. This will encourage more customers to shop hence improved market share. The SMS platform can also be used to give after sales services and other personalized information and birthday wishes. All these will increase customer satisfaction.
Keywords: 650; Short Message Services(SMS) installment platform; customer satisfaction